Inactivation of the Pore-Forming Toxin Sticholysin I by Peroxynitrite: Protection by Cys Groups Incorporated in the Toxin - Lissi-Gervaso, E (Springer New York LLC, 2014)
Sea anemones synthesize a variety of toxic peptides and proteins of biological interest. The Caribbean Sea anemone Stichodactyla helianthus, produces two pore-forming toxins, Sticholysin I (St I) and Stichloysin II (St II), with the ability to form oligomeric pores in cell and lipid bilayers characteristically lacking cysteine in their amino acid sequences. Recently, two mutants of a recombinant variant of Sticholysin I (rSt I) have been obtained with a Cys residue in functionally relevant regions for the pore-forming activity of the toxin: r St I F15C (in the amino terminal sequence) and r St I R52C (in the binding site). Aiming at characterizing the effects of oxidants in toxins devoid (r St I) or containing –SH moieties (r St I F15C and r St I R52C), we measured their hemolytic activity and pore forming capacity prior and after their incubation with peroxynitrite (ONOO?). At low ONOO?/Toxin ratios, nearly 0.8 Trp groups are modified by each added peroxynitrite molecule, and the toxin activity is reduced in ca. 20 %. On the other hand, in –SH bearing mutants only 0.5 Trp groups are modified by each peroxynitrite molecule and the toxin activity is only reduced in 10 %. The results indicated that Cys is the initial target of the oxidative damage and that Trp residues in Cys-containing toxins were less damaged than those in r St I. This relative protection of Trp groups correlates with a smaller loss of hemolytic activity and permeabilization ability in liposomes and emphasizes the relevance of Trp groups in the pore forming capacity of the toxins. © 2014, Springer Science+Business Media New York.